Analysis of deposit of physiological and psychological theories of forming motive skills on development of theory of teaching to the physical drills - Khudolii O.N (Kharkov National Pedagogical University, 2010)
Influence of different theories is certain on the construction of process of teaching motive actions of young gymnasts. The results of complete factor experiment are presented. They allowed to formulate principle settings to the construction of process of teaching the physical drills of young gymnasts at the age 7-13 years old. On the construction of teaching process influences more in all: theory of functional systems (43%, р<0,001), theory of construction of motions (41%,р<0,001), theory of management mastering of knowledge, forming actions and concepts (2,6%, р<0,05). The positive effect of teaching depends on the successive decision of tasks of teaching and rational application of methods.